What Is the Current State of Awareness, Knowledge, and Attitudes Toward Breast Cancer? A Cross-Sectional Survey Among Health and Non-health College Students - Islam, Md. Ashraful; AlShayban, Dhfer Mahdi; Nisa, Zeb-un-; Al-Hawaj, Ghadeer Abdulwahab Mohammed; Al-Eid, Ghadeer Hani Ali; Alenazi, Atheer Mohammed Moqbel; Malik, Zubda; Maqsood, Muhammad Bilal; Ishaqui, Azfar Athar; Akbar, Zahida; Iqbal, Muhammad Shahid; Hossain, Mohammad Akbar; et al. (Frontiers in Public Health, 2022)
Objective To document breast cancer (BC) knowledge, awareness, and attitudes among female undergraduate students studying at health and non-health colleges. Methods A 3-month cross-sectional study was conducted among female undergraduate students studying at health and non-health subject colleges affiliated to a public university. Convenience sampling was employed, and a previously validated questionnaire available in English and Arabic languages was used. Multiple linear regression was used to report the predictors of BC knowledge. A two-tailed p-value of < 0.05 was considered significant. The study was approved by an ethics committee. Results A total of 506 responses were analyzed. The mean knowledge score was 13.98 ± 4.1. The findings of the surveyed students suggested that more than 55% of the students had an acceptable level of knowledge. By education sector, approximately 70% and 40% of health and non-health college students, respectively, had an acceptable level of knowledge. The mean difference in knowledge scores between students of health and non-health colleges was significant (p < 0.001) as students at health colleges had a higher score. Age, college type and the presence of the disease in family/relatives were significant predictors of students' BC knowledge (p < 0.05). Conclusion By comparing it with previous evidence, the knowledge of BC has improved. The role of awareness campaigns as an information medium for students from non-health backgrounds is greatly appreciated. Moreover, the internet and electronic media have emerged as new sources of information for non-health college students, and therefore, more efforts are needed to utilize this medium in empowering this student population in understanding of this disease.